Clinical Syndromes of Peripheral Nervous System Neurotoxicity from Immune-Checkpoint Inhibitors - Isaac Smith; Minna Choi; Sakinah Sabadia (Seminars in Neurology, 2026)
Abstract The introduction of immune checkpoint inhibitors (ICIs) has dramatically changed the landscape of treatment for a variety of cancers. However, there is increasing recognition of neurotoxicity related to ICI use. In this review, we will discuss the peripheral nervous system neurologic immune related adverse events (PNS-nirAEs) of anti-CTLA4, anti-PD1, and anti-PDL1 ICIs, including nerve, neuromuscular junction, muscle, and overlap syndromes. We will discuss the relevant epidemiology, pathophysiology, clinical syndromes, diagnostic approaches, treatment, and prognosis of PNS-nirAEs. We will discuss the safety and efficacy of ICIs when utilized in patients with pre-existing neurologic autoimmune disorders (NAIDs). Lastly, we will discuss relevant treatment options and when to consider rechallenging with ICI after an initial de novo PNS-nirAE or exacerbation of a pre-existing NAID.